Die Alpen im Jahr 2020 - Psenner, Roland (alpine space - man and environment, 2006)
This book summarizes the results of an interdisciplinary meeting held in Obergurgl in 2006. Based on current knowledge the meeting aimed at a research strategy for the research focus "alpine space - man and environment" of Innsbruck University.